THE NURSING CARE OF THE CLIENT WITH HIV/AIDS IN A UNIVERSITY HOSPITAL IN THE 1980’s - Neves, Claudinéa Lacerda da Rosa (2009)
ABSTRACT: Research about nurses strategies to set up the nursing care to clients with HIV / AIDS in the Gaffrée and Guinle Hospital, of the Federal University of the State of Rio de Janeiro, from 1983 to 1987. Objectives: to analyse the strategies undertaken by nurses with the challenge of caring for clients with HIV/AIDS in this hospital, and discuss the symbolic effect of these strategies for the recognition of the importance of nurses in the care of clients with HIV / AIDS. Social-historical study, with nine nurses who were involved with the care of clients with HIV/AIDS. Results: We demonstrated that the lack of knowledge about HIV / AIDS, fear and discrimination were the main barriers to nursing care to clients, in the early years of the epidemic, in the wards of the hospital, but nurses do not have struck, they were to search for updated habitus. Conclusion: Since this moment, nurses have become spokesmen of care to clients with HIV/AIDS and started to reorganize the nursing care in this hospital wards, that makes possible to offer clients with HIV/AIDS a humanized and decent care guided by the respect for the human being and appreciation of life. Descriptors: History of Nursing, nursing care, nursing.